Analysis of resonant fast ion distributions during combined ICRF and NBI heating with transients using neutron emission spectroscopy. (26th March 2018) - Hellesen, C.; Mantsinen, M.; Conroy, S.; Ericsson, G.; Eriksson, J.; Kiptily, V. G.; Nabais, F.
Abstract: ICRF heating at the fundamental cyclotron frequency of a hydrogen minority ion species also gives rise to a partial power absorption by deuterium ions at their second harmonic resonance. This paper studies the deuterium distributions resulting from such 2nd harmonic heating at JET using neutron emission spectroscopy data from the time of flight spectrometer TOFOR. The fast deuterium distributions are obtained over the energy range 100 keV to 2 MeV. Specifically, we study how the fast deuterium distributions vary as ICRF heating is used alone as well as in combination with NBI heating. When comparing the different heating scenarios, we observed both a difference in the shapes of the distributions as well as in their absolute level. The differences are most pronounced below 0.5 MeV. Comparisons are made with corresponding distributions calculated with the code PION. We find a good agreement between the measured distributions and those calculated with PION, both in terms of their shapes as well as their amplitudes. However, we also identified a period with signs of an inverted fast ion distribution, which showed large disagreements between the modeled and measured results. Resonant interactions with tornado modes, i.e. core localized toroidal alfven eigenmodes (TAEs), are put forward as a possible explanation for the inverted distribution.